Katalikų Bažnyčia Lietuvoje 1940-1990 metais: tarp pasipriešinimo ir prisitaikymo - Streikus, Arūnas (Lietuvos istorijos studijos, 2009)
In spite of suffered losses on the eve of the Soviet reoccupation, the Catholic Church in Lithuania remained one of the most important actors that hindered sovietisation of the social and cultural life during the first years of the Soviet rule. Just in the beginning of the 1950s, the regime was able to cut off all ties connecting the Church with society (publication of religious literature, religious education of youth, involvement of lay people), but in spite of this, the Church was representing further in the eyes of many Lithuanians not only religious contents, but also national values. This mantle of superficial respect hid lowering knowledge of the Church teaching and growing indifference towards it. Due to the long-lasting oppression and isolation from the outside world, the Church retreated into a hard shell, which offered a reliable protection against attacks of the Soviet regime but hardly fit when facing the challenges of an open society.Nevertheless, even in these unfavourable conditions, there managed to survive shoots of a new life that led to cherish hopes for the future. Firstly, the new period of Church resistance in the 1970s, which took the shape of a believers' rights movement, raised a new generation of conscious lay Catholics. Secondly, the defense of believers' rights was not only the fight for religious liberty but also raised civic as well as national self-consciousness and questioned the norms of Soviet ethics. Thirdly, the necessity to unite forces against the Soviet regime, which was limiting the space of religious and national activities, helped to overcome ethnoconfessional seclusion of the Lithuanian Catholic community, thus opening the way for inter-cultural dialogue.